Analisis Yuridis Prasyarat Pembentukan Tim Seleksi KPU dan BAWASLU Tahun 2022 Perspektif Siyasah Dusturiyah - Faozan, Fizay Muhamad (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2023)
The Presidential Decree Number 120/P of 2021 regarding theformation of the selection team for candidates of KPU and Bawaslu for the periodof 2022-2027 is not in accordance with Article 22 Paragraph 3 of Law Number 7of 2017. Article 22 Paragraph 3 stipulates that the composition of the selectionteam for candidates of KPU/Bawaslu consists of 3 government officials, 4academics, and 4 members of the public. The findings of this study state that: 1)The formation of the selection team for candidates of KPU and Bawaslu for theperiod of 2022-2027 is not in accordance with one of the requirements in LawNumber 7 of 2017 concerning elections, namely Article 22 Paragraph 3; 2) Theimpact of all decisions made by the selection team can be considered illegalbecause they are not in accordance with the applicable law, and the selectionresults can be declared null and void. Furthermore, the composition of theselection team can cause conflicts of interest; 3) The review of Siyasah Dusturiyah,in accordance with Surah An-Nisa Verse 58 and the principle that